2019
DOI: 10.12998/wjcc.v7.i16.2143
|View full text |Cite
|
Sign up to set email alerts
|

Application of Newcastle disease virus in the treatment of colorectal cancer

Abstract: Colorectal cancer (CRC) is one of the main reasons of tumor-related deaths worldwide. At present, the main treatment is surgery, but the results are unsatisfactory, and the prognosis is poor. The majority of patients die due to liver or lung metastasis or recurrence. In recent years, great progress has been made in the field of tumor gene therapy, providing a new treatment for combating CRC. As oncolytic viruses selectively replicate almost exclusively in the cytoplasm of tumor cells and do not require integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 83 publications
(82 reference statements)
0
24
0
1
Order By: Relevance
“…The vaccine was prepared from the cells of the operated liver metastases. The curves of % metastasis-free survival demonstrate that immunotherapy has a significant tertiary prevention effect [32][33][34]. Figure 1C shows recent results that were obtained from patients suffering from glioblastoma multiforme (GBM).…”
Section: Three Examples For Vaccination-induced Long-term Protective mentioning
confidence: 91%
“…The vaccine was prepared from the cells of the operated liver metastases. The curves of % metastasis-free survival demonstrate that immunotherapy has a significant tertiary prevention effect [32][33][34]. Figure 1C shows recent results that were obtained from patients suffering from glioblastoma multiforme (GBM).…”
Section: Three Examples For Vaccination-induced Long-term Protective mentioning
confidence: 91%
“…Strategies such as using oncolytic viruses in vivo and in vitro or tumor cells infected with oncolytic viruses release PAMPs, which increases immune responses ( 217 , 218 ). The results of phase I and II trials showed that the use of Newcastle virus-infected tumor cells reduced recurrence and increased OS in CRC patients ( 44 , 219 ). However, the high levels of self-antigens present in tumor lysates cause the lack of specificity of immune responses and increase the possibility of promoting autoimmune responses, limiting the use of this method in susceptible individuals ( 220 , 221 ).…”
Section: Personalized Immunotherapy In Crcmentioning
confidence: 99%
“…The NDV envelope protein and other intracellular factors induce an immune response to elicit a potent anti-tumor effect in a variety of cancers including CRC. Genetic modification of NDV could enhance this tumor lysis activity or could allow NDV to act as a vector for delivery of therapeutic genes [101].…”
Section: Oncolytic Virus Therapymentioning
confidence: 99%